A Nonparametric Test for the Equivalence of Populations Based on a Measure of Proximity of Samples - Klyushin, D. A.; Petunin, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We propose a new measure of proximity of samples based on confidence limits for the bulk of a population constructed using order statistics. For this measure of proximity, we compute approximate confidence limits corresponding to a given significance level in the cases where the null hypothesis on the equality of hypothetical distribution functions may or may not be true. We compare this measure of proximity with the Kolmogorov–Smirnov and Wilcoxon statistics for samples from various populations. On the basis of the proposed measure of proximity, we construct a statistical test for testing the hypothesis on the equality of hypothetical distribution functions.